(untitled) (Plant Tissue Culture and Biotechnology, 2026)
Molecular evaluation of mango (Mangifera indica L.) genotypes plays a vital role in shaping effective strategies for enhancing productivity, conserving genetic resources, and improving germplasm for future breeding efforts. In this context, a study was conducted to genetically characterize 18 mango genotypes (BARI Aam-1 to BARI Aam-18) using eleven ISSR (Inter Simple Sequence Repeat) markers. The ISSR analysis produced a total of 67 bands, of which 51 were polymorphic, indicating a high level of genetic variability with an average polymorphism rate of 76.11%. The overall genetic diversity and Shannon’s information index were calculated at 0.446 and 0.636, respectively, further confirming substantial genetic variation among the genotypes. Genetic distance analysis revealed the closest relationship between BARI Aam-1 and BARI Aam-18 (0.008), while the most distant relationship was observed between BARI Aam-6 and BARI Aam-11 (0.836). Likewise, genotype similarity indices showed the highest similarity (0.991) between BARI Aam-17 and BARI Aam-18 and the lowest (0.443) between BARI Aam-6 and BARI Aam-11. Based on UPGMA cluster analysis, the genotypes were divided into two major groups: Cluster I comprised BARI Aam-11, BARI Aam-12, and BARI Aam-7, while Cluster II included the remaining fifteen genotypes. This comprehensive description of genetic variation and relationship among mango genotypes may provide great value for future studies, breeding initiatives, and the development of improved cultivars. Plant Tissue Cult. & Biotech. 35(2): 267-276, 2025 (December)